2006
DOI: 10.1227/01.neu.0000208955.12461.c7
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Atlantoaxial Fixation with a Polyaxial Screw-rod Construct: Technical Case Report

Abstract: Placement of C1 lateral mass and C2 pedicle screws using minimally invasive techniques is technically feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 10 publications
0
14
0
1
Order By: Relevance
“…There are few cases reported in the literature. [8][9][10][11] Wang reported on 3 cases of single-level posterior cervical fusion on traumatic instability achieved through a METRx® tube (Medtronic Sofamor Danek, Memphis, TN). 9 Fong et al reported on two additional patients with trauma requiring a posterior cervical tension band through a METRx® tube.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few cases reported in the literature. [8][9][10][11] Wang reported on 3 cases of single-level posterior cervical fusion on traumatic instability achieved through a METRx® tube (Medtronic Sofamor Danek, Memphis, TN). 9 Fong et al reported on two additional patients with trauma requiring a posterior cervical tension band through a METRx® tube.…”
Section: Discussionmentioning
confidence: 99%
“…Joseffer et al described the use of the Quadrant™ retractor (Medtronic Sofamor Danek, Memphis, TN) to deliver unilateral C1-2 screws for fixation of an Os Odontoideum. 10 The largest series on MIS posterior cervical instrumentation is described by Wang et al 8 They retrospectively reviewed their first 18 patients treated with this technique with two year follow-up. Half of their patients were treated with a single level and half with two-level.…”
mentioning
confidence: 99%
“…Several studies of the safety and the biomechanical stability of the posterior cervical lateral mass screw have been published 6,12,22,28) . Moreover, the application of the posterior lateral screw fixation method became easier as a result of the development of the polyaxial screw-rod system 7,15,19,21,27) . .…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported that posterior lateral mass screw fixation provides biomechanical stability equal to those of anterior plating or the posterior wiring technique 6,12,22,28) . Moreover, the application of posterior lateral screw fixation became easier as a result of the development of the polyaxial screw-rod system 7,13,19,21,27) . Since the first description of the technique by Roy-Camille et al in 1972, several lateral mass screw fixation techniques have been suggested by Louis, Magerl, Anderson and An 1,2,17,23) .…”
Section: Introductionmentioning
confidence: 99%
“…The screw fixation and fusion of the first and second cervical vertebras can also effectively be achieved using a tube. There was a report on effective fixation of posterior C1 lateral mass and C2 pedicle screws for Os odontoideum patients 17) . They were alble to insert a C1 lateral mass screw and rod while positioning the tube and adjusting the angle around the C2 lateral mass.…”
Section: Instrumentation Of the Cervical Spinementioning
confidence: 99%